2019
DOI: 10.33423/jop.v19i2.2043
|View full text |Cite
|
Sign up to set email alerts
|

Skills Needed by New Accounting Graduates in a Rapidly Changing Technological Environment

Abstract: Current research indicates that newly-hired accounting graduates may lack some of the skills necessary to be successful in their chosen profession. This paper examines recent research to determine what skills are needed by accounting graduates. A number of papers suggest that accounting graduates may not have the soft skills, such as analytical thinking skills and communication skills, necessary to succeed. This may be due in part to differences between Millennial students and students of prior generations Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Furthermore, providing access to modern technologies can help to bridge the gap between traditional teaching methods and the rapidly changing needs of the modern workforce (Bressler & Pence, 2019). In today's economy, the ability to adapt to new technologies and think creatively is a valuable skill that is highly sought-after by employers.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, providing access to modern technologies can help to bridge the gap between traditional teaching methods and the rapidly changing needs of the modern workforce (Bressler & Pence, 2019). In today's economy, the ability to adapt to new technologies and think creatively is a valuable skill that is highly sought-after by employers.…”
Section: Resultsmentioning
confidence: 99%
“…The employability of accounting graduates has recently emerged as a hot topic for multiple reasons, including the adoption of IFRS (Senan, 2019) and the direct consequences of liberalization and globalization. Recent literature through multiple studies has repeatedly shown that the current accounting education fails to meet various stakeholders' requirements (Atanasovski et al, 2018;Bressler and Pence, 2019;Rastogi et al, 2019). Solutions to this compelling issue can be arrived at only through a different set of various stakeholders' approaches and mindsets.…”
Section: Discussionmentioning
confidence: 99%
“…Several experts have attempted to identify the skills required to enhance accounting employability (Bressler and Pence, 2019;Crawford et al, 2011;Paguio and Jackling, 2016;Phan et al, 2021;Silva et al, 2021). Most of these studies have delved around commercial awareness, analytical, teamwork, communication, presentation and problem-solving skills.…”
Section: Employability In Accountingmentioning
confidence: 99%
“…A study carried out by Domingos (2017) with accounting final-year students concluded that the five most developed general competences during their academic training were (i) teamwork, (ii) the ability to work under pressure, (iii) time management, (iv) interpersonal competences, and (v) organizational competences. Bressler and Pence (2019) asserted that accounting graduates may not have the necessary competences, particularly social competences, to succeed in the profession. The authors claimed that the reason may be related to the differences between millennial students and students from previous generations.…”
Section: Development Of General Competences In Higher Educationmentioning
confidence: 99%
“…In the last two decades, research has suggested that education in this area is outdated and that curricula do not meet employers' expectations and needs; therefore, there is no harmony with real-world requirements (Albrecht & Sack, 2000;Aryanti & Adhariani, 2020;Derekoy, 2019;Getahun & Mersha, 2020;Jackling & de Lange, 2009;Kavanagh & Drennan, 2008;Lim et al, 2019). Faced with the new challenges of the accounting profession, other studies have focused on the competences that accounting graduates are currently required to have due to the rapid changes in the technological environment (Bressler & Pence, 2019;Dwaase et al, 2020;Pan & Seow, 2016).…”
Section: Introductionmentioning
confidence: 99%